Therapies and Vaccines Based on Nanoparticles for the Treatment of Systemic Fungal Infections - Kischkel, Brenda; Rossi, Suélen A.; Santos, Samuel R.; Nosanchuk, Joshua D.; Travassos, Luiz R.; Taborda, Carlos P. (Frontiers in Cellular and Infection Microbiology, 2020)
Treatment modalities for systemic mycoses are still limited. Currently, the main antifungal therapeutics include polyenes, azoles, and echinocandins. However, even in the setting of appropriate administration of antifungals, mortality rates remain unacceptably high. Moreover, antifungal therapy is expensive, treatment periods can range from weeks to years, and toxicity is also a serious concern. In recent years, the increased number of immunocompromised individuals has contributed to the high global incidence of systemic fungal infections. Given the high morbidity and mortality rates, the complexity of treatment strategies, drug toxicity, and the worldwide burden of disease, there is a need for new and efficient therapeutic means to combat invasive mycoses. One promising avenue that is actively being pursued is nanotechnology, to develop new antifungal therapies and efficient vaccines, since it allows for a targeted delivery of drugs and antigens, which can reduce toxicity and treatment costs. The goal of this review is to discuss studies using nanoparticles to develop new therapeutic options, including vaccination methods, to combat systemic mycoses caused by Candida sp., Cryptococcus sp., Paracoccidioides sp., Histoplasma sp., Coccidioides sp., and Aspergillus sp., in addition to providing important information on the use of different types of nanoparticles, nanocarriers and their corresponding mechanisms of action.